Regenerative Medicine and Cell Therapy - Baharvand, Hossein; Aghdami, Nasser (Stem Cell Biology and Regenerative Medicine, 2013)
This volume presents an overview of the latest advances in the field of regenerative medicine and cell therapy, spanning topics such as neurological, ocular surface, skin, cardiac, musculoskeletal, liver, and gastrointestinal diseases and diabetes, in addition to germ line and cord blood stem cells. The chapters have been written by renowned experts in the field of regenerative medicine, and are considered a valuable resource for biomedical researchers and clinicians.   Readership: Scientists in the field of regenerative medicine, clinicians and specialists, and patients or the general public who wish to seek additional information about specific treatment options.